The The Existence of Turun Ranjang Marriage as an Effort to Enhance Family Harmony in Bakeong Village, Guluk-Guluk, Sumenep - Khairiyatin, Khairiyatin; Hatta, Fitri Annisa; Jannah, Raudatul; Nurdiansyah, Eko Wahyu (MAQASIDI: Jurnal Syariah dan Hukum, 2024)
The main problem in this study is the existence of the practice of off-the-cuff marriage to achieve family harmony which especially occurs in the Bakeong Guluk-Guluk Sumenep community (case study in Bakeong Guluk-Guluk Sumenep village). Turun ranjang marriage itself is a marriage carried out by a husband or wife with a sibling of his or her deceased partner. The purpose of this study is to find out the description of turun ranjang marriage in Bakeong village with the motifs behind it and the existence of turun ranjang marriage in family harmony. This research is a field research with a type of qualitative research that is descriptive. The data collection method was carried out through observation and interviews. The results of this study show that the practice of turun ranjang in marriage is carried out after one of the husband or wife dies, and is religiously valid. Then the thing behind this marriage is the desire of the parties for the benefit of the child. Then the existence of turun ranjang marriage to family harmony is quite influential on the happiness of children and the harmony of a family.